Determinant of Job Satisfaction and Job Performance among Staff of An Islamic Banks - Wulandari, Elisa; Adiba, Elfira Maya; Septiana, Nurul Izzati (Journal of Islamic Economic Laws, 2023)
Human resources in a company is a valuable asset that needs attention to achieve maximum performance so that company goals are achieved. Satisfied employees will affect their performance. There is still a lack of research on the relationship between internal and external factors and job satisfaction and human resource performance, particularly regarding the current popular topic of work-life balance and what young employees want from their jobs. This study aims to determine the effect of Islamic leadership, Islamic work environment, Islamic work motivation, and work-life balance on employee satisfaction and performance at Islamic banks. This study used a quantitative approach with a sampling, namely simple random sampling. The number of samples in this study was 41 respondents. Data analysis techniques use SEM-PLS using SmartPLS to manage data. The results showed that Islamic leadership variables greatly influence employee job satisfaction, work environment variables, work-life balance, and work motivation have a small influence on job satisfaction. In contrast, job satisfaction variables have a large influence on employee performance. The findings of this study are anticipated to be an assessment of Islamic bank stakeholders' attention to their human resources to maximize job satisfaction and performance and hasten the achievement of the company's objectives. The construction of a supportive Islamic workplace environment and work-life balance are issues that require consideration to promote employee satisfaction and performance.